Predicting the Speed, Scale, and Range of Information Diffusion in Twitter - Yang, Jiang; Counts, Scott (Conference: Proceedings of the Fourth International Conference on Weblogs and Social Media, 2010)
We present results of network analyses of information diffusion on Twitter, via users’ ongoing social interactions as denoted by “@username” mentions. Incorporating survival analysis, we constructed a novel model to capture the three major properties of information diffusion: speed, scale, and range. On the whole, we find that some properties of the tweets themselves predict greater information propagation but that properties of the users, the rate with which a user is mentioned historically in particular, are equal or stronger predictors. Implications for end users and system designers are discussed.